2001
DOI: 10.1055/s-2001-18866
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Factor Pathway in Disseminated Intravascular Coagulation

Abstract: In most instances, tissue factor (TF) exposed to the circulation is the sole culprit underlying the initiation of disseminated intravascular coagulation (DIC), although notable exceptions because of a more direct activation of the coagulation system, by snake venoms, for example, do occur. Peripheral monocytes and subendothelial structures are the potential sources of such TF; in the former, TF emerges on the cell surface on synthesis induction and in the latter it becomes available subsequent to permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 94 publications
1
106
1
6
Order By: Relevance
“…Recently it was shown that E. coli-induced TF expression on human monocytes and TF activity in plasma microparticles was C5a-dependent (39). This may be of great importance, as the formation of microparticles seems to reflect the severity of DIC (40,41). There is evidence that expression of TF is also dependent on TLR4/MD-2 signal transduction (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that E. coli-induced TF expression on human monocytes and TF activity in plasma microparticles was C5a-dependent (39). This may be of great importance, as the formation of microparticles seems to reflect the severity of DIC (40,41). There is evidence that expression of TF is also dependent on TLR4/MD-2 signal transduction (42).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin also exerts direct effects on cells to regulate platelet aggregation, endothelial cell activation, and smooth muscle cell (SMC) 1 proliferation via interactions with members of the protease-activated receptor (PAR) family, such as PAR1, PAR2, PAR3, and PAR4, known as G-protein-coupled receptors (2,3). However, the intracellular signaling cascades downstream from the thrombin receptors are surprisingly complex and are still not well understood.…”
mentioning
confidence: 99%
“…Thrombin belongs to the multifunctional serine protease family and plays an important role in the blood coagulation cascade through the cleavage of fibrinogen to fibrin (1,2). Thrombin also exerts direct effects on cells to regulate platelet aggregation, endothelial cell activation, and smooth muscle cell (SMC) 1 proliferation via interactions with members of the protease-activated receptor (PAR) family, such as PAR1, PAR2, PAR3, and PAR4, known as G-protein-coupled receptors (2,3).…”
mentioning
confidence: 99%
“…Insoluble fibrin generation also closes the capillary gate and disrupts perfusion and oxygenation in organs and tissues (see "Capillary Gate Component" below). This causes stroke [195,196], mental disturbances [197,198], myocardial infarction [195,[199][200][201][202] …”
Section: Open Accessmentioning
confidence: 99%